Fourth Five Year Plan Revised Outlay 1969-74 - Planning Commission (Planning Commission, 1970)
The National Development Council at its meeting held on April 19-20 1969, while approving the Draft Fourth Plan 1969-74, directed that the Planning Commission should make a further assessment of the States resources after the award of the Fifth Finance Commission had been received. It also directed that the debt position of the States vis-a-vis the Centre should be reviewed. An important development since the publication of the Draft Fourth Plan has been the nationalisation of 14 major commercial banks. The Government decision on the recommendations of the Fifth Finance Commission was announced on August 29, 1969. The Planning Commission thereafter held a series of discussions with the State Governments during September-November 1969 at the official level and later with the Chief Ministers during November-December 1969.
Paper for the National Development Council Government of India Planning Commission